Engineering stable electrocatalysts by synergistic stabilization between carbide cores and Pt shells - Göhl, Daniel; Garg, Aaron; Paciok, Paul; Mayrhofer, Karl; Heggen, Marc; Shao-Horn, Yang; Dunin-Borkowski, Rafal E.; Román-Leshkov, Yuriy; Ledendecker, Marc (Nature Materials, 2019)
Core–shell particles with earth-abundant cores represent an effective design strategy for improving the performance of noble metal catalysts, while simultaneously reducing the content of expensive noble metals1–4. However, the structural and catalytic stabilities of these materials often suffer during the harsh conditions encountered in important reactions, such as the oxygen reduction reaction (ORR)3–5. Here, we demonstrate that atomically thin Pt shells stabilize titanium tungsten carbide cores, even at highly oxidizing potentials. In situ, time-resolved experiments showed how the Pt coating protects the normally labile core against oxidation and dissolution, and detailed microscopy studies revealed the dynamics of partially and fully coated core–shell nanoparticles during potential cycling. Particles with complete Pt coverage precisely maintained their core–shell structure and atomic composition during accelerated electrochemical ageing studies consisting of over 10,000 potential cycles. The exceptional durability of fully coated materials highlights the potential of core–shell architectures using earth-abundant transition metal carbide (TMC) and nitride (TMN) cores for future catalytic applications.
CRIS-Team Scopus Importer:2019-12-31